2016
DOI: 10.1007/s12598-016-0777-5
|View full text |Cite
|
Sign up to set email alerts
|

Formation mechanism of titanium and niobium carbides in hardfacing alloy

Abstract: The most effective carbide-forming elements titanium and niobium were added into hardfacing alloy. Formation and composition of carbides in the hardfacing alloy were investigated by means of optical microscope (OM), scanning electron microscope (SEM), X-ray diffraction (XRD) and energy-dispersive spectrometer (EDS). Hardness and impact toughness of the hardfacing alloy were measured. The thermodynamics and formation mechanism of carbides were also discussed. It is found that the carbides consist of TiC and NbC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…To increase the impact toughness of electric arc coatings by grain refinement the microstructures, the authors [3] propose to introduce Ti and Nb additives allowing for the formation of appropriate carbide phases to the composition of coatings based on low-carbon high-chromium steel. Research results revealed that the addition of a total of ~0.16 % by mass of Nb and ~0.26 % by mass of Ti can increase impact viscosity toughness by 1.6 times, while the hardness of coatings does not change.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…To increase the impact toughness of electric arc coatings by grain refinement the microstructures, the authors [3] propose to introduce Ti and Nb additives allowing for the formation of appropriate carbide phases to the composition of coatings based on low-carbon high-chromium steel. Research results revealed that the addition of a total of ~0.16 % by mass of Nb and ~0.26 % by mass of Ti can increase impact viscosity toughness by 1.6 times, while the hardness of coatings does not change.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…However, under work-ing conditions, in which there are even minor dynamic and (or) cyclic loads, the use of such materials is limited due to the high fragility of coarse-grained metal carbide eutectic structure. For such conditions, it is rational to use electrode materials, the structure of which corresponds to the systems of alloying impact resistant steels [1][2][3][4][5]. The most common representatives of such steels are high-manganese (>13 % by mass of Mn) austenitic steels, which are strengthened during…”
Section: Introductionmentioning
confidence: 99%
“…Instead, the eutectic structure could be obviously refined and partial chromium carbides were replaced by Ti carbides, which benefited a higher wear resistance. Yang et al [21] prepared the Fe-Cr13-C hardfacing alloy containing Ti and Ni elements. They found that the TiC and NbC were the main carbides that caused the refinement of martensite matrix and therefore contributed to an improved hardness and toughness in the metal.…”
Section: Introductionmentioning
confidence: 99%
“…Devido as propriedades mecânicas como elevada dureza e baixa densidade, o acréscimo de titânio com elemento adicional ou principal do fluxo, tem sido amplamente abordado pela literatura [1][2][3][4][5]. Comparado a outros tipos de carbonetos como carbonetos de cromo (Cr7C3), carbonetos de tungstênio (WC) e carbonetos de boro (B4C), os carbonetos de titânio se apresentam com melhores propriedades de resistência ao desgaste [6][7][8].…”
Section: Introductionunclassified